Factorial Invariance of the Social Anxiety Screening Scale (EDAS) in Spanish and Chilean adolescents - Piqueras, José Antonio; Olivares, José; Vera Villarroel, Pablo; Marzo, Juan Carlos; Kuhne, Walter (Anales de Psicología / Annals of Psychology, 2012)
This instrumental study examines factorial invariance of the Scale for Social Anxiety Screening (EDAS) across countries and gender in two samples of Chilean and Spanish adolescents between 14 and 17 years using multigroup confirmatory factor analysis. The sample consisted of 1185 Spanish adolescents, with a mean age of 15.49 years (SD=1.10) and the Chilean sample consisted of 965 adolescents, whose age mean age was 15.51 (SD=1.09). The age and gender distribution was homogeneous. Results showed that EDAS showed a good fit to a three factors model (Avoidance, Anxiety and Interference), representing each subscale a single dimension. No significant differences between Chilean and Spanish ado- lescents attributable to the countries and gender. The reliability coefficients were high in each of the subscales. The results provide empirical evidence for the reliability, validity and factorial invariance of the EDAS in Spanish and Chilean adolescents.